ANALYSIS OF STUDENT CHARACTER IN SCIENCE SUBJECTS AT LAMPUYANG STATE ELEMENTARY SCHOOL, PULO ACEH DISTRICT - Lisnawati; Mayang Sari; Mhd. Syafii; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In character education, students can be taught and assisted in the process of forming character and ethical values. Character education can be implemented one way through science learning. The aim of this research was to find out how much interest students have in carrying out the learning process at school, especially science subjects, because this subject is one of the lessons that must be completed at elementary school level. What the researchers used as topics for interviews with students were, (1) Analyzing students' understanding in science lessons, (2) Analyzing students' interest in science material. The research method used is a descriptive qualitative method, namely research based on phenomena that occurred in one case of the Lampuyang State Elementary School, Pulo Aceh District. The research results obtained are very satisfying, where students do not think that science subjects are difficult and should be liked and studied and teachers can provide material that is easy to understand so that one day science lessons become the favorite subject of all students at Lampuyang State Elementary School, Pulo Aceh District.